Analytical of the press discourse of the Israeli war on Gaza 2023 (Al-Aqsa Flood) in the Palestinian newspaper: Al-Quds Newspaper as a model - Alshaqaqi, Ahmad Abdulaziz (Journal of Humanities & Social Sciences, 2025)
The study sought to achieve a main objective, which is: monitoring, interpreting, and analyzing the journalistic discourse in Al-Quds newspaper regarding its coverage of the Al-Aqsa Flood War, in addition to its effects, and revealing the most important strategies used. The study relied on the media survey method, and used the method of analyzing journalistic discourse over a period of one year. The study sample reached (254) opinion articles.  The most important results were: The journalistic discourse on the war on the Gaza Strip addressed several theses, the most important of which was the scenarios of future conflict with the occupation in the first place. The study showed that opinion article writers during the study period relied on political and analytical discourse in order. The article writers also rely heavily on the strategy of sensing danger. In addition to the advancement of logical proof paths over illogical proof paths,the most important of which is the position of decision makers. The study recommended the need to pay attention to the importance of humanitarian discourse, as well as the importance of article writers using strategies consistent with their arguments, as well as ensuring diversity in frames of reference, which enriches and enhances the importance of these materials.
Keywords: journalistic discourse; Palestinian newspapers; Al-Quds newspaper